PHARMACOLOGICAL THERAPY AS A PREVENTION EFFORT FOR COVID-19 FOR HIGH SCHOOL/SMK STUDENTS IN WEST JAVA AND LAMPUNG IN DEALING WITH NEW HABITS AND FACE TO FACE - Mufti, Mufti fauzi Rahman (Universitas INABA, 2023)
The Covid-19 pandemic has significantly impacted various aspects of society, including health, economy, and education. This paper focuses on the challenges faced in the field of education, particularly in the implementation of online learning. Insufficient network coverage and limited internet access in certain areas have hindered the effectiveness of online learning. Additionally, students have faced additional stressors such as the depletion of internet packages, overwhelming homework assignments, and piled-up school tasks, leading to academic stress. In response to these challenges, there is a need to provide education related to the prevention and treatment of Covid-19 to students. To address these issues and prepare for future face-to-face learning, a community service program was implemented through four stages. The preparatory stage involved the formation of community service groups, surveying and analyzing potential locations for community service, coordination with schools and other supporting parties, and program socialization. The implementation stage focused on providing educational and outreach programs to high school students in West Java and Lampung, including the deployment of community service teams, provision of necessary facilities and infrastructure, and the execution of community service activities.